PELAKSANAAN PELAYANAN DASAR BIMBINGAN DAN KONSELING PADA SMA DI KOTA METRO TAHUN AJARAN 2012/2013 - Lilis Puspitaningrum; Syarifuddin Dahlan; ratna Widiastuti (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The purpose of this study was to describe the implementation of a guidance and counseling at senior high school in Metro City in academic year 2012/2013.The problem of this research is the implementation of guidance and counseling service at senior high school in Metro City was not maximum. The problem was the